STUDI WAKTU PELAYANAN KAPAL DI DERMAGA I PELABUHAN BAKAUHENI - Galuh Pramita; Nurwanda Sari (JICE (Journal of Infrastructural in Civil Engineering), 2020)
Bakauheni Port, located in Lampung Province, is the ferry ports serving ships from Sumatra Island heading to Java Island or vice versa. In general case, the problem of service performance often encounteres in port operations. Ineffective management of the port is one of the obstacles in service. The queue system of waiting ships during docking activity is one of the result of ineffective management of the ports operations. The purpose of this study was to calculate the time taken by ship in maneuvering, raise and drop off passengers at the Pier I of the Bakauheni Port. The research was conducted by surveys at dock I of the Bakauheni Port during the normal condition. Data were analysed so as to know the operational time required for loading and unloading ships and maneuver. Based on data analysis, it can be concluded that the headway value of each ship operating at Pier I is: Suki 59,50 minutes, BSP I 56,45 minutes, Mustika Kencana 50,13 minutes, HM Baruna 53,64 minutes, Jatra 2 45,91 minutes, 45,91 minutes and Shalem 44,97 minutes. The average headway of the ships at Pier I was 51,77 minutes. From the value, it shows the operating in Pier I Bakauheni Port has already reached optimum due to total time needed less than the time determined by Bakauheni Port with a total  24 ship trip in Pier I.